The global politics of the environment - Elliott, Lorraine M. (Mac Millan, 1998)
What kinds of international institutions are best suited to dealing with global environmental problems? How can we address the crisis of state capacity? What role should non-state actors have in environmental governance? Why are women and indigenous peoples still marginalized in global environmental politics? What are the consequences of the global ecological crisis for economic and security policies?